2022
DOI: 10.3390/foods11070924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corruption Control on the Number of Undernourished People in Developing Countries

Abstract: Developing countries will be home to 85% of the world’s population by 2030. Hence, it is important to ensure food security for them. This effort is not easy, as the number of undernourished people (NUP) in the world has increased. We investigated the impact of food and non-production factors on the NUP in developing countries. This study employed secondary data from 57 developing countries between 2002 and 2018. These countries come from three regions, namely Africa, Asia, and Latin America and the Caribbean. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 114 publications
(198 reference statements)
0
3
0
1
Order By: Relevance
“…Increased agricultural production has been shown to increase food availability and income, thereby increasing food security and decreasing PUN (Abdallah et al 2021). Furthermore, CP does not affect PUN in Africa and LAC because it is influenced not only by food availability but also by the ease of food access (Nugroho et al 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased agricultural production has been shown to increase food availability and income, thereby increasing food security and decreasing PUN (Abdallah et al 2021). Furthermore, CP does not affect PUN in Africa and LAC because it is influenced not only by food availability but also by the ease of food access (Nugroho et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…While the dependent variable in this study is the prevalence of undernourishment (the probability that one person is found to be regularly consuming an amount of food that provides less than his or her dietary energy requirements). Based on Nugroho et al (2022), the prevalence of undernourishment can represent food security in a country; therefore we use this variable in our study. The sources of the variables are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Porém, os fatores mais agravantes para a população mais vulnerável são: a desigualdade social, concentração de renda, queda do poder aquisitivo da população, poder e apropriação de terras (capital natural) (PENA, 2022), desacelerações econômicas, altos preços dos alimentos e a corrupção endêmica. Há dados na literatura que indicam que há relação entre as práticas de corrupção e a insegurança alimentar, pois a corrupção aumenta a insegurança alimentar, consequentemente afeta a expectativa de vida, prejudica a paz e a estabilidade (UCHENDU et al, 2015;NUGROHO et al, 2022).…”
Section: Alimentação Para Todos (Fome) E Condição De Vida Decente (Mi...unclassified
“…Instead, these essential sources of nutrients are being replaced with foods and drinks with high sugar, fat, and salt since they are cheaper and more readily available (Masipa, 2017;Rahaman et al, 2021). Additionally, the COVID-19 pandemic has compounded food security issues, furthering the increased vulnerability to food insecurity, especially among the poorly resourced countries and the less-privileged (Nugroho et al, 2022;Grote et al, 2021). Furthermore, the global recession has disrupted the global food supply chains which makes it more challenging to cater for large food imports of some countries especially countries of SSA (Grote et al, 2021).…”
Section: Introductionmentioning
confidence: 99%